Determination of the Optimal Position of Pendulums of an Active Self-balancing Device - Ziyakaev G. R. Gregory Rakitovich; Kazakova O. A. Oksana Aleksandrovna; Yankov V. V.; Ivkina O. P. (2017, 2017)
Title screen